Spaceflight dynamics / William E Wiesel - Wiesel, William E
Designed for undergraduate courses in spacecraft dynamics and orbital mechanics, this new edition offers a three-dimensional treatment of dynamics discussions of rigid body dynamics, rocket trajectories, and the space environment. An expert in his field, author William E. Wiesel presents a wealth of information in an easy-to-understand manner without the daunting mathematical rigor of graduate texts. Reference is made to actual flight vehicles and satellites to give students background on the type of work currently being done in this field